2014
DOI: 10.1158/0008-5472.can-14-0803
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Smad3 Phosphorylation Events That Affect Malignant and Metastatic Behaviors in Breast Cancer Cells

Abstract: Smad3, a major intracellular mediator of TGFb signaling, functions as both a positive and negative regulator in carcinogenesis. In response to TGFb, the TGFb receptor phosphorylates serine residues at the Smad3 C-tail. Cancer cells often contain high levels of the MAPK and CDK activities, which can lead to the Smad3 linker region becoming highly phosphorylated. Here, we report, for the first time, that mutation of the Smad3 linker phosphorylation sites markedly inhibited primary tumor growth, but significantly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 42 publications
(67 reference statements)
4
35
0
Order By: Relevance
“…It has been shown that among the MCF‐10A series of cell lines, the TGF‐β/activin‐SMAD pathway has cytostatic effects in the premalignant and low‐grade breast carcinoma line MCF10A (M‐II and M‐III), whereas it enhances metastasis in a high‐grade breast cancer line MCF10A M‐IV . Introduction of a SMAD3 mutant with phosphorylation‐resistant mutations in the linker was reported to inhibit primary tumor growth, but it significantly increased lung metastasis of MCF10A M‐IV . This was in contrast to the results reported for a SMAD3 mutant with a truncated C‐terminus (Smad3ΔC), which functions as dominant negatives .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that among the MCF‐10A series of cell lines, the TGF‐β/activin‐SMAD pathway has cytostatic effects in the premalignant and low‐grade breast carcinoma line MCF10A (M‐II and M‐III), whereas it enhances metastasis in a high‐grade breast cancer line MCF10A M‐IV . Introduction of a SMAD3 mutant with phosphorylation‐resistant mutations in the linker was reported to inhibit primary tumor growth, but it significantly increased lung metastasis of MCF10A M‐IV . This was in contrast to the results reported for a SMAD3 mutant with a truncated C‐terminus (Smad3ΔC), which functions as dominant negatives .…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β in complex with its type I and type II receptors, leads to activation of Smad proteins, with an important role in the mammary development and tumorigenesis (,). We showed that CM from cytokines‐primed hASCs induced phosphorylation and nuclear translocation of Smad3 in MCF‐7 cells, thus supporting previous findings which showed that Smad3 phosphorylation can be induced by direct cell contacts/interactions between bone marrow MSCs and colorectal cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…To see the effect of Smad3 linker phosphorylation on TGF‐β responses and Smad3 transcriptional activity, a high‐grade human breast cancer cell line (MCF‐10CA1a.cl1, hereafter known as CA1a) in culture was first treated with a pan‐CDK inhibitor, flavopiridol. TGF‐β transcriptional activity was significantly upregulated by treatment with flavopiridol concomitant with reduction of Smad3 linker phosphorylation at T179, S204, and S208, suggesting that Smad3 linker phosphorylation negatively regulates Smad3 transcriptional activity as determined by (CAGA) 12 ‐luciferase ([CAGA] 12 ‐Luc) reporter assay (Figure B) . Likewise, inhibition of Smad3 linker phosphorylation by a specific phosphatase (SCP1) acting on the Smad2/3 linker region has resulted in upregulation of TGF‐β signaling …”
Section: Smad3 Phosphorylation At Serine/threonine Residues In the C‐mentioning
confidence: 98%
“…It was initially reported that Ras‐induced Smad2/3 linker phosphorylation inhibits TGF‐β‐induced responses by interrupting nuclear translocation of Smad2/3 and subsequent Smad‐dependent transcription . Direct evidence that Smad3 linker phosphorylation suppresses TGF‐β responses comes from studies using a Smad3 mutant at linker phosphorylation sites . We have adopted recombinant adenoviruses constitutively expressing wild‐type Smad3 (Ad‐Smad3) or its mutant at the linker region (Ad‐EPSM), the C‐terminal (Ad‐3SA) or both the linker and the C‐terminal (Ad‐EPSM/3SA), in which all serine and threonine phosphorylation sites are replaced with alanine (A) and valine (V), respectively (Figure A) .…”
Section: Mutation At Smad3 Linker Phosphorylation Sites Greatly Enhanmentioning
confidence: 99%
See 1 more Smart Citation